Irreversible electroporation induces CD8+ T cell immune response against post-ablation hepatocellular carcinoma growth. (10th April 2021) - Dai, Zihao; Wang, Zongren; Lei, Kai; Liao, Junbin; Peng, Zhenwei; Lin, Manxia; Liang, Ping; Yu, Jie; Peng, Sui; Chen, Shuling; Kuang, Ming
Abstract: Ablative treatment evokes antitumor immunity, but knowledge on the emerging irreversible electroporation (IRE)-induced immunity in hepatocellular carcinoma (HCC) is limited. To investigate the immune effects induced by IRE and its role in preventing post-ablation HCC progression, a C57BL/6J mouse model bearing subcutaneous H22 hepatoma was employed. IRE treatment significantly suppresses HCC growth, and treated mice are tumor-free after secondary tumor injection and show increased splenic interferon-gamma (IFN-γ)+CD8 + T cells. Additionally, more CD8 + T and dendritic cells, but not CD4 + T, B or NK cells, infiltrate into peri-ablation zones after IRE at day 7. Depletion of CD8 + T cells induces local tumor regrowth and distant metastasis after IRE. Vaccination using IRE-processed H22 lysates prevents tumorigenesis in mice, suggesting a protective immune response. IRE also alleviates immunosuppression by reducing local and splenic Treg and PD-1 + T cells. Regarding mechanism, IRE induces cell necrosis and significant release of danger-associated molecular patterns including ATP, high mobility group box 1 and calreticulin that are pivotal to CD8 + T cell immunity. Together, IRE is a promising approach to evoke CD8 + T cell immunity, which help prevent post-ablation HCC progression. Highlights: Irreversible electroporation elicits CD8 + T cell immunity in a murine hepatoma model. The induced immunity is long-lasting and against hepatocellular carcinoma growth. Irreversible electroporation reduces Treg and PD-1 + T cells in tumors and spleens. Irreversible electroporation promotes danger-associated molecular patterns release.